The analysis of applying theoretical provisions of trucking for the description of autotransport enterprises’ functioning in a current mode - L. S. Trofimova; V. V. Anokhin (Вестник СибАДИ, 2017)
The article shows the results of the analysis of trucking’s acting theoretical provisions on calculation of a rolling stock’s productivity and cost. It has been established that the existing theoretical provisions of trucking are assigned for changeable daily schedule of a rolling stock’s work. It is necessary to develop a methodology that allows considering opportunity of using unit of a rolling stock in trucking under specific agreement.